2007
DOI: 10.1515/jpm.2007.002
|View full text |Cite
|
Sign up to set email alerts
|

How useful is 3D and 4D ultrasound in perinatal medicine?

Abstract: 3DUS and 4DUS provided additional information for the diagnosis of facial anomalies, evaluation of neural tube defects, and skeletal malformations. Additional research is needed to determine the clinical utility of 3DUS and 4DUS for the diagnosis of congenital heart disease, central nervous system (CNS) anomalies and detection of fetal neurodevelopmental impairment assessed by abnormal behavior in high-risk fetuses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(67 citation statements)
references
References 113 publications
1
66
0
Order By: Relevance
“…3D images can be rotated for viewing from different angles and may benefit lay audiences as organs and structures are easily identifiable. The literature suggests there is interest in the specific potential of 3D images to have greater utility in communicating with patients, as such images are assumed to be easier to understand [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…3D images can be rotated for viewing from different angles and may benefit lay audiences as organs and structures are easily identifiable. The literature suggests there is interest in the specific potential of 3D images to have greater utility in communicating with patients, as such images are assumed to be easier to understand [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22] The availability of new diagnostic data has in an extraordinary way raised our knowledge about intrauterine life, substantially modifying some earlier interpretations. 23 First spontaneous fetal movements can be observed with conventional two-dimensional ultrasound (2D US) around 8th gestational week, while the newly developed 4D US allows the visualization of fetal motility one week earlier (Table 2). 24 General movements are the first complex fetal movement patterns observable by 2D US.…”
Section: The Origin Of Fetal Behavior and Fetal Motor Development Assmentioning
confidence: 99%
“…[19][20][21][22][23][24][25]27,[28][29][30][31] In order to better understand fetal neurobehavioral patterns, we have learned a lot form basic studies of brain development and from clinical postnatal studies of neonates. Now, when we have reached the edge of fetal behavioral investigation by 4D ultrasonography in normal fetuses, we intend to find some new ideas and ways of investigation presenting neonatal aspect of fetal neurology.…”
Section: Neonatal Aspect Of Fetal Neurologymentioning
confidence: 99%
See 1 more Smart Citation
“…Their analysis revealed that 3D and 4D US is advantageous in evaluation of the facial anomalies, neural tube defects, skeletal malformations, congenital heart disease, central nervous system (CNS) anomalies and fetal neurodevelopmental impairment perceptible by abnormal behavior in high-risk fetuses. 13 Visualization of the fetal face became one of the major interests in the domain of three-dimensional ultrasonography. Due to their affection in malformation syndromes and chromosomal abnormalitie, regions of special interest are fetal maxilla, mandible arch, ear and nose.…”
mentioning
confidence: 99%